2005
DOI: 10.2214/ajr.185.2.01850400
|View full text |Cite
|
Sign up to set email alerts
|

Needle Tract Implantation After Sonographically Guided Percutaneous Biopsy of Hepatocellular Carcinoma: Evaluation of Doubling Time, Frequency, and Features on CT

Abstract: The doubling times of extrahepatic needle tract implantation of malignant neoplasms after sonographically guided percutaneous biopsy for HCC were similar to those of typical HCCs in the liver on CT-based analysis. The frequency was relatively low, and their CT features were similar to those reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 18 publications
2
66
0
1
Order By: Relevance
“…27,32 In studies looking at the risk of seeding, a long follow-up period (up to 4 years) is essential. 28,33,34 In a large series, the incidence of needle tract seeding in more than 1000 patients with HCC was 0.76%. 34 Other studies with more than 100 patients have reported the incidence of tumor seeding following biopsy was in the range of 1.6%-3.4%.…”
Section: Risk Of Needle Tract Seedingmentioning
confidence: 99%
See 1 more Smart Citation
“…27,32 In studies looking at the risk of seeding, a long follow-up period (up to 4 years) is essential. 28,33,34 In a large series, the incidence of needle tract seeding in more than 1000 patients with HCC was 0.76%. 34 Other studies with more than 100 patients have reported the incidence of tumor seeding following biopsy was in the range of 1.6%-3.4%.…”
Section: Risk Of Needle Tract Seedingmentioning
confidence: 99%
“…28,33,34 In a large series, the incidence of needle tract seeding in more than 1000 patients with HCC was 0.76%. 34 Other studies with more than 100 patients have reported the incidence of tumor seeding following biopsy was in the range of 1.6%-3.4%. 35 Percutaneous biopsy of HCC carries a potential risk of tumor seeding along the needle tract.…”
Section: Risk Of Needle Tract Seedingmentioning
confidence: 99%
“…One requirement for inclusion was that all malignancies needed to be proven by histology, and the needle type and the followup had to be known as well. They excluded all case reports and patients with seeding after ethanol 19 (2008) Systematic review Histology 3a Durand et al 13 (2001) Prospective and consecutive Histology Good Yes 1b Caturelli et al 12 (2004) Prospective and consecutive Histology Good Yes 1b Huang et al 17 (1996) Retrospective and nonconsecutive Histology Good Yes 3b Takamori et al 24 (2000) Retrospective and nonconsecutive Histology Good Yes 3b Maturen et al 23 (2006) Retrospective and nonconsecutive Histology Good Yes 3b Kosugi et al 22 (2004) Retrospective and nonconsecutive Histology Good Yes 3b Kim et al 21 (2000) Retrospective and nonconsecutive Histology Good Yes 3b Chapoutot et al 20 (1999) Retrospective and nonconsecutive Histology Good Yes 3b Chang et al 26 injection and radiofrequency ablation and all patients with suspected intrahepatic seeding. Finally, they included 8 studies, which were mostly retrospective cross-sectional studies.…”
Section: Question 2 What Are the Complications Of Tumor Biopsy?mentioning
confidence: 99%
“…12,13,17,[20][21][22][23][24] We identified 4 more studies. [25][26][27][28] Three of these studies were not analyzed because the reference standard was poorly defined 27,28 or some of the patients were not followed up. 25 In all, we included 1 systematic review and 9 single studies in the analysis (Tables 3 and 4).…”
Section: Question 2 What Are the Complications Of Tumor Biopsy?mentioning
confidence: 99%
“…Liver biopsy procedure is like any other procedure has some complications including but not limited to hemorrhage, perforation, infection, death and seeding of the tumors [4,5]. Very few cases reported the implantation/seeding of the original HCC following the liver biopsy or RFA and incidence is estimated to be 2.1-5% with a mean time for seeding is estimated between 8 and 48 months.…”
Section: Discussionmentioning
confidence: 99%